The Synthesis of Truncated Polypeptides for Immune Surveillance and Viral Evasion - Cardinaud, Sylvain; Starck, Shelley R.; Chandra, Piyanka; Shastri, Nilabh (PLOS ONE, 2010)
Background Cytotoxic T cells detect intracellular pathogens by surveying peptide loaded MHC class I molecules (pMHC I) on the cell surface. Effective immune surveillance also requires infected cells to present pMHC I promptly before viral progeny can escape. Rapid pMHC I presentation apparently occurs because infected cells can synthesize and present peptides from antigenic precursors called defective ribosomal products (DRiPs). The molecular characteristics of DRiPs are not known. Methodology/Principal Findings Here, using a novel method for detecting antigenic precursors and proteolytic intermediates, we tracked the synthesis and processing of Epstein-Barr Virus encoded nuclear antigen 1 (EBNA1). We find that ribosomes initiated translation appropriately, but rapidly produced DRiPs representing ∼120 amino acid truncated EBNA1 polypeptides by premature termination. Moreover, specific sequences in EBNA1 mRNA strongly inhibited the generation of truncated DRiPs and pMHC I presentation. Significance Our results reveal the first characterization of virus DRiPs as truncated translation products. Furthermore, production of EBNA1-derived DRiPs is down-regulated in cells, possibly limiting the antigenicity of EBNA1.